Faktor-Faktor yang Berhubungan dengan Kepatuhan Membayar Iuran BPJS Kesehatan Oleh Peserta Mandiri di Unit Rawat Jalan RS Sumber Waras Tahun 2024 - Mutiara Febia Wulandari; Dwi Nurmawaty; Anggun Nabila; Susi Shorayasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Compliance of independent BPJS Kesehatan participants in paying contributions is important to ensure access to health services. Factors such as lack of knowledge, low income, negative perceptions of BPJS Health benefits, and constraints on access to payment can cause delays or arrears of contributions. This study aims to identify factors associated with compliance with paying BPJS Kesehatan contributions for independent participants in the Outpatient Unit of Sumber Waras Hospital in 2024. This study used a cross-sectional study method with a quantitative approach. A sample of 86 respondents was collected using a questionnaire. Analysis techniques include univariate and bivariate analysis with the Chi-Square test. The results showed 54.7% of participants did not comply with paying contributions. A total of 59.3% had good knowledge, 66.3% had an income < UMR, 62.8% had a positive perception of the benefits of BPJS Kesehatan, and 55.8% used online payment access. The results of bivariate analysis showed an association between knowledge (p=0.001), income (p=0.000), perception of BPJS Health benefits (p=0.000), and access to payment (p=0.002) with compliance to pay contributions. This study suggests further exploration of the effect of financial education or incentive policies on compliance with paying BPJS Kesehatan contributions.